Analisis Strategi Pemasaran Pembiayaan Murabahah Pada Produk Cicilan Emas Dalam Meningkatkan Jumlah Nasabah Pada BSI Diponegoro Surabaya - Iqbal Ramadhani; Ceta Indra lesmana; Makinun Amin (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
This study aims to analyze the marketing strategy of murabahah financing on gold installment products in increasing the number of customers at Bank Syariah Indonesia (BSI) KCP Diponegoro Surabaya. The method used is descriptive qualitative with data collection techniques through interviews, observation, and documentation. The research informants consist of bank internal parties (Branch Operational and Relationship Manager) and customers of the gold installment product. The results show that the marketing strategy using the 7P marketing mix (product, price, place, promotion, people, process, and physical evidence) has contributed to the increase in the number of customers from 2021 to 2023. The challenges faced include low public literacy regarding the murabahah contract, competition with other financial institutions, and gold price fluctuations. This study confirms that the application of appropriate sharia-based marketing strategies can increase product attractiveness and strengthen customer loyalty